A New Genetic Fibrinogen Variant (Fibrinogen Erfurt I) Structurally Characterized by an Abnormal Bβ-Chain and Present both in Plasma and Platelets - Meyer, M; Schellenberg, I; Vogel, G; Bischoff, I (Thrombosis and Haemostasis, 1988)
An abnormal fibrinogen was discovered in the plasma of a clinically asymptomatic woman. This fibrinogen variant was analyzed by high resolution two–dimensional gel electrophoresis and its molecular abnormality established consisting in a slight decrease in molecular mass of the Bβ–chains. Analysis of fibrin revealed that cleavage of fibrinopeptide B by thrombin is normal, the molecular defect being confined to the β–portion of the Bβ–chain. The same fibrinogen variant was detected in the blood platelets of the proposita. This finding supports the assumption of a common origin of plasma and platelet fibrinogen pools. Family studies revealed the presence of the abnormal fibrinogen in a brother of the proposita, thus confirming the genetic nature of the observed variant. The underlying mutant gene occurs in both carriers in heterozygous state.
Keywords: Fibrinogen; Fibrinogen variant; Dysfibrinogenemia